School Leadership and Mathematics Performance - Chieng, Yi Shi (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This research investigated the relationships between domains of school leadership and UPSR mathematics performance. It also determined the differences in school leadership and UPSR mathematics performance based on the types and locations of the schools. This research used the cross-sectional survey, with comparative and correlational designs. Seventy-seven teachers from eight primary schools were the samples for this study. A questionnaire was administered once to the samples and the UPSR mathematics performance for year 2007 was obtained from the school management. Pearson-product moment correlations were used to measure the relationships between domains of school leadership and UPSR mathematics performance while independent t-tests were used to determine the differences in school leadership and UPSR mathematics performance based on the types and locations of the schools. The results showed that all the domains of school leadership were interrelated except the relationships between transformational leadership and teachers' commitment to school-community partnerships, collective teacher efficacy and teachers' commitment to school as a professional learning community, and collective teacher efficacy and teachers' commitment to school-community partnerships. The results also showed that only two domains of school leadership, which were transformational leadership and teachers' commitment to school as a professional learning community, were positively correlated with UPSR mathematics performance. Moreover, these two domains also showed significant differences in school leadership based on the types of schools. However, only collective teacher efficacy showed significant difference in school leadership based on the locations of the schools. Other results indicated that there was significant difference in UPSR mathematics performance based on the types of schools but not on the locations of the schools.